Microtextured surfaces in higher loaded rolling-sliding EHL line-contacts. (November 2018) - Marian, Max; Tremmel, Stephan; Wartzack, Sandro
Abstract: Due to scarce resources coupled with increasing mobility requirements, resource-efficient machine and motor elements are vital. Therefore, surfaces in lubricated tribological contacts can be microtextured, enabling improved lubricating conditions and friction behavior. While this has already been shown for lower loaded contacts, the effects for higher loaded, application-oriented EHL contacts are topic of basic research. Therefore, geometrically defined microtextures are adapted to the tribological system of the tappet/camshaft contact in the valve train of combustion engines as a demonstrator. The tribological performance in respect to lubricating conditions, friction and wear behavior is analyzed on single cam/tappet component test-rigs. EHL simulation is used as 'numerical zoom' into a section of the contact area contributing to better understanding of effects and observed phenomena. Highlights: Microtextures offer potential for friction reduction in higher loaded EHL line-contacts with high amount of sliding. Lubricating conditions and friction behavior result from the complex interplay of microtexture dimensions and arrangement. Microtextures are preserved in long-run tests, deeper microtextures show higher wear rates. EHL simulation is used as 'numerical zoom' in the contact area in order to explain local effects induced by microtextures.